Impact of Hospital Volume and the Experience of Endoscopist on Adverse Events Related to Endoscopic Retrograde Cholangiopancreatography: A Prospective Observational Study - Hyun Jik Lee; Chang Min Cho; Jun Heo; Min Kyu Jung; Tae Nyeun Kim; Kook Hyun Kim; Hyunsoo Kim; Kwang Bum Cho; Ho Gak Kim; Jimin Han; Dong Wook Lee; Yoon Suk Lee (Gut and Liver, 2020)
Background/Aims: Few studies have addressed the relationship between the occurrence of adverse events (AEs) in endoscopic retrograde cholangiopancreatography (ERCP) and hospital case volume or endoscopist’s experience with inconsistent results. The aim of our study was to investigate the impact of hospital case volume and endoscopist’s experience on the AEs associated with ERCP and to analyze patient- and procedure-related risk factors for post-ERCP AEs. Methods: From January 2015 to December 2015, we prospectively enrolled patients with naïve papilla who underwent ERCP at six centers. Patient- and procedure-related variables were recorded on data collection sheets at the time of and after ERCP. Results: A total of 1,191 patients (median age, 71 years) were consecutively enrolled. The overall success rate of biliary cannulation was 96.6%. Overall, 244 patients (20.5%) experienced post-ERCP AEs, including pancreatitis (9.0%), bleeding (11.8%), perforation (0.4%), cholangitis (1.2%), and others (0.9%). While post-ERCP pancreatitis (PEP) was more common when the procedure was performed by less experienced endoscopists, bleeding was more common in high-volume centers and by less experienced endoscopists. Multivariate analysis showed that a less experience in ERCP was significantly associated with PEP (odds ratio [OR], 1.630; 95% confidence interval [CI], 1.050 to 2.531; p=0.030) and post-ERCP bleeding (OR, 1.439; 95% CI, 1.003 to 2.062; p=0.048). Conclusions: Our study demonstrated that overall AEs following ERCP were associated with the experience of the endoscopist. To minimize post-ERCP AEs, rigorous training with a sufficient case volume is required, and treatment strategies should be modified according to the endoscopist’s expertise.